DEVELOPING ONLINE ASSESSMENT FOR JUNIOR HIGH SCHOOL STUDENTS USING PROPROFS DURING THE COVID19 PANDEMIC - Dewi Sri Ayu Ramdini; Filzanadilla Dwi Putri; Muhamad Nurdin; Radisti Aulia Zhahra; Siti Nur Annisa; Yulia Setianingsih; Rizdika Mardiana (STKIP Muhammadiyah Bogor, 2021)
The covid-19 virus pandemic has made the world of education change the learning system, from face-to-face learning to online learning. This study aims to develop an online assessment to test students' abilities on the material that has been given online. Interviews with English teachers and collecting documents from the internet are data collection techniques used in this study. Some of the steps that are taken to obtain the results of online assessment development on grade 7, 8, 9 are: (1) The process of reviewing the curriculum and textbooks so that the scope of the questions is determined, namely core competence and basic competence for grades 7, 8, 9. (2) Making questions based on the grid using the Proprofs application. (3) Making an answer key. The making of this answer key is carried out simultaneously with the second stage. The weaknesses and strengths of Proprofs used in creating and developing online assessments are the results of this study.